Rise above : leadership lessons from the RAF - Jupp, John (Pearson, 2021)
"Leadership is much in demand in our modern society, in business, in government, in the charities and in the military. The RAF has, for the British military, a short history of just 100 years, during which time it has faced huge challenges: wars for survival, complicated wars on foreign soil, complex peacekeeping missions, humanitarian efforts and the extraction of British citizens from the wars of others. It has dealt with enormous societal upheaval, technological change and organisational restructuring (both expanding and contracting). Through it all it has remained successful. That success is due in great part to its leadership. The RAF leadership model provides detail of the behaviours, knowledge and skills that leaders need to be successful"--